Neighborhood and community battery projects: A systematic analysis of their current state and future prospects - Mohanty A.; Ramasamy A.K.; Verayiah R.; Mohanty S. (Elsevier Ltd, 2025)
Neighborhood and community battery projects signify a fundamental change in the way energy is controlled and distributed within local communities. These initiatives are distinguished by their inventive approach to tackling the obstacles of incorporating renewable energy, maintaining grid stability, and involving the community. The uniqueness of study in this field originates from its comprehensive and integrated methodology, which takes into account not only the technical features of energy storage systems but also the economic, social, and regulatory variables that impact their adoption and functioning. A notable feature of research in this field is its focus on actively involving and including the community. Neighborhood and community battery projects aim to empower communities by engaging them in decision-making processes and providing incentives for their participation in energy storage programs, thus enabling them to take charge of their energy future. This approach, which focuses on the community, not only enhances the acceptability and implementation of energy storage devices but also cultivates a feeling of ownership and accountability for the energy system. In summary, the research conducted on neighborhood and community battery projects is characterized by its creative methodology, with the goal of establishing energy systems that are both sustainable and robust, resulting in benefits for both communities and the environment. There is a scarcity of scholarly articles in the existing literature that specifically examine the evaluation of community and neighborhood battery systems. This study aims to provide a thorough examination of the breadth and issues associated with community and neighborhood batteries. ? 2024